Development of an objective achievement test to assess the assessment competencies of the elementary school teacher - Khenniche, Youcef; Tebbaa, Farouk (Journal of Human Sciences, 2023)
The training system in Algeria lacks objective assessment tools to verify the competencies of its teachers and diagnose their professional needs, for this reason the development of reliable tests is of great necessity. The purpose of this study was to develop a test contains of 36 multiple choice items, and that it was applied on 12 teachers. In order to examine the validity, we used judges, the coefficient of Cramer and Phi, and the discrimination index of agreement, as the reliability was measured by the test-retest method. The results revealed that the items have a discriminatory capacity that exceeds the minimum required, and that the test has acceptable content and criterion validity, and acceptable reliability. Based on the results, the test can be used to assess teachers’ competencies assessment.